New species of Acanthocinini Blanchard, 1845 (Coleoptera, Cerambycidae, Lamiinae) from Ecuador and notes on Parabaryssinus lineaticollis (Gounelle, 1910) - Nascimento, Francisco E. De L.; Mcclarin, Jim (Zootaxa, 2018)
Three new species of Cerambycidae from Ecuador are described and illustrated: Nealcidion napoensis sp. nov, Pseudosparna triangulata sp. nov and Leptocometes longilineatus sp. nov. Notes on Parabaryssinus lineaticollis (Gounelle, 1910) and a description of the female of this species are provided.